PENGEMBANGAN E-MODUL BERBASIS STREAM (SCIENCE, TECHNOLOGY, RELIGI, ENGINEERING, ART, AND MATHEMATICS) PADA MATERI MINYAK BUMI - M Agus Syafelyn; Neti Afrianis M.Pd (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2026)
Innovations that are in line with developments are greatly needed in the independent learning process where students are not only recipients of the material delivered by educators but are also the center of learning. . This research aimed at designing and developing valid and practical STREAM (Science, Technology, Religion, Engineering, Art, Mathematics)-based e-module based on validity test by material and media experts, as well as practicality test by teachers and students. It was Research and Development (R&D) with 4-D (Define, Design, Development and Disseminate) development model. This research was conducted to the eleventh-grade students of IPA Robotik class at State Islamic Senior High School 1 Pekanbaru. The media validation results showed that the percentage score was 87.5%, and the material expert obtained a score 90.8% with very valid criterion. Then, the result of the practicality test by the teacher showed the score 93.2% with very practical category, and the result of the practicality test of students was 88.9% with very practical category. So, it could be identified that STREAM-based e-module on Crude Oil lesson could be used as a supporting medium for chemistry learning